Innovation of a Hot Steam Boiling System to Increase the Productivity of Anchious Fish Processing in the Ombak Badabuih Fishermen Group in Pesisir Selatan - Delima Yanti Sari; Fitrah Qalbina; Melri Deswina; Suci Andri (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Anchovies are small pelagic fish belonging to the order Malacopterygi and family Clupeidae, with lengths ranging from 40–145 mm. They have thin, easily detached scales, a silvery lateral line located between the pectoral and pelvic fins, and are commonly found in coastal waters. West Sumatra Province consists of both marine and land areas, with several coastal regencies, including Pesisir Selatan Regency, which has a coastline of approximately 201.8 km. In Koto XI Tarusan District, about 80% of the population relies on fishing as their main livelihood. Anchovy fishing is typically conducted at night using floating bagan gear with a 1 mm mesh size. Preservation methods include boiling, salting, drying, smoking, and cooling. A survey of the Ombak Badabuih Fishermen’s Group in Simpang Ampang Pulai, Koto XI Tarusan District, revealed that fishermen face limitations due to inadequate anchovy boiling equipment. The current tools use thin metal plates, wood covers, and clay pans that must be replaced every three months, resulting in high costs and reliance on firewood as fuel. Therefore, this community service program aims to innovate a stainless-steel anchovy boiling system to improve product quality and enhance the fishermen’s economic conditions.